2018
DOI: 10.1073/pnas.1811858115
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modes of derepression of an Arabidopsis immune receptor complex by two different bacterial effectors

Abstract: SignificancePlants and animals carry intracellular nucleotide-binding leucine-rich repeat (NLR) immune receptors. How NLR receptors activate defense on perceiving pathogen molecules is poorly understood, especially in plants. Some NLRs function in pairs, with one NLR carrying a domain that mimics a pathogen effector target. Effector action on this domain activates the second “helper” NLR. In the Arabidopsis RPS4 and RRS1 pair, RRS1 carries a WRKY transcription factor domain targeted by bacterial effectors AvrR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 39 publications
(58 reference statements)
3
119
0
5
Order By: Relevance
“…In rice, the BIK1 orthologs OsRLCK176 and OsRLCK185 were shown to associate with OsCERK1 to mediate the chitin and peptidoglycan‐triggered immune signaling (Couto and Zipfel 2016; Li et al 2017). In addition to the RLCK group VII members, Arabidopsis RLCK group XII members BR‐SIGNALING KINASE 1 (BSK1) and BSK5 have also been reported to play a crucial role in PTI by interacting with PRRs directly (Shi et al 2013; Majhi et al 2019; Zhao et al 2019).…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%
“…In rice, the BIK1 orthologs OsRLCK176 and OsRLCK185 were shown to associate with OsCERK1 to mediate the chitin and peptidoglycan‐triggered immune signaling (Couto and Zipfel 2016; Li et al 2017). In addition to the RLCK group VII members, Arabidopsis RLCK group XII members BR‐SIGNALING KINASE 1 (BSK1) and BSK5 have also been reported to play a crucial role in PTI by interacting with PRRs directly (Shi et al 2013; Majhi et al 2019; Zhao et al 2019).…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%
“…Some regions appear to be the source of major Cf loci, like MW, which are able to generate multiple effector-specific RLPs (RIVAS AND THOMAS 2005;DE WIT et al 2009). Although distinct recognition of multiple effectors by one or more R proteins is known (MACKEY et al 2002;MA et al 2018), the opposite has only been observed as convergent evolution in different species (ASHFIELD et al 2014;SAUCET et al 2015;CARTER et al 2018) with only one recent example in closely related species (AGUILERA-GALVEZ et al 2018). However, considering the monomorphic nature of Ecp5 and level of genetic complexity observed amongst Cf-Ecp5 genes in this study, we have to address this slight paradox in terms of evolution.…”
Section: Discussionmentioning
confidence: 92%
“…It is notable that there are differences in the mechanistic basis of AvrRps4 and PopP2 recognition (Sarris et al ., ; Ma et al ., ). RRS1‐R/RPS4 appears to be an exquisitely coevolved NLR pair; whether autoimmunity and ETI can be uncoupled in other NLRs remains to be seen.…”
Section: Discussionmentioning
confidence: 97%
“…It is notable that there are differences in the mechanistic basis of AvrRps4 and PopP2 recognition Ma et al, 2018). RRS1-R/RPS4 appears to be an exquisitely coevolved 6 The SUSHI mutations in the RRS1B Toll/interleukin-1 receptor (TIR) domain do not affect AvrRps4 recognition.…”
Section: Researchmentioning
confidence: 99%